The optimisation of a 15 kV 4H-silicon carbide integrated gate commutated thyristor - Cao, Qinze; Gammon, Peter Michael; Renz, Arne Benjamin; Zhang, Luyang; Baker, Guy; Antoniou, Marina; Lophitis, Neophytos (My University, 2022)
A 15kV SiC thyristor is analysed, considering for the first time the design properties that will ensure the safe, stable operation of the device as an integrated gate commutated thyristor (IGCT), while also minimizing its on-state losses. Key to the optimization is ensuring that, during the turn-off phase, minority carrier charge is commutated via the base to the gate, rather than flowing into the cathode, thus reducing large switching losses, and an unstable transition period. This is made possible in the design presented via the introduction of a highly doped base strip (HDBS), which provides a low resistance channel between the centre of the cathode and the gate. This innovation allows the cathode to be extended, such that it makes up 90% of the top surface, thus minimising on-state losses.
Keywords: IGCT; optimization; Silicon carbide; simulation; thyristor